Leprosy on the scalp - Raila de Brito Macedo; Tárcio Santos; Paulyane Bezerra Sampaio Ramos; Daniela Mayumi Takano; Virgínia Sampaio Madeiro Leal (Sociedade Brasileira de Dermatologia, 2016)
Abstract Leprosy is a chronic infectious disease caused by Mycobacterium leprae. This bacillus has a high predilection for skin and peripheral nerves. The scalp's anatomical properties do not favor the development of such mycobacterium. We report a case of leprosy with scalp involvement, a rare occurrence in our literature.